Stakeholder Engagement in the Steel Industry: The key to unlocking the resources and markets of tomorrow, today - Postma, Tobin (2008)
The emergence of developing countries, specifically Brazil, Russia, China and India, is pushing the demand for steel to new heights. This comes at the same time as steel consumption is decreasing in developed markets such as the USA and Canada, emphasizing the importance these new markets are having on the growth of the steel industry. As leaders in the steel industry, both in terms of revenue and output, this is especially important for ArcelorMittal. With a growth strategy that relies heavily on vertical integration, entry into new markets and accessing the resources they contain is essential to the future success of the company. However, these markets and the resources within them are controlled by various stakeholder groups, whose expectations and visions are often conflicting but who can collectively determine whether or not ArcelorMittal's plans go forward. Thus it is imperative that ArcelorMittal proactively engages with these stakeholders and involve them in its decision making processes as this will increase the likelihood of it gaining access to resources and entry to new markets and possibly result in a sustained competitive advantage. Currently, there appears to be a gap in how effective ArcelorMittal's current stakeholder engagement strategies are perceived to be by some stakeholder groups, a perception that whether or not is justified, could jeopardise ArcelorMittal's 'social licence' to operate. After building a business case for stakeholder engagement and then analyzing and discussing this perceived gap and its implications for the company, this study puts forward recommendations that will help ArcelorMittal identify relevant stakeholder issues and then effectively engage on them, recommendations that include: - Developing a system for indentifying internal and external stakeholders, both at a global level and at a local level, and then classify them based on their importance to the company's business strategy - Develop global and local stakeholder engagement strategies that emphasize proactive, two-way communication - Enter into more partnerships with NGOs and Industrial Bodies in an effort to gain insight into current best practices for stakeholder engagement, especially in the mining sector - Utilise the internet and intranet to develop interactive engagement tools that can also provide customised information for specific stakeholder groups - Develop an online resource centre for ArcelorMittal's Corporate Responsibility practitioners that provides relevant materials and tools needed in order to create and implement local stakeholder engagement plans